Pemberdayaan Perempuan melalui Pelatihan Manajemen Sumber Daya Manusia dan Pemasaran Digital di Sekolah Perempuan (SEKOPER) Mojokerto - Ahfi Nova Ashriana; Elly Joenarni; Anna Kridaningsih; Yusuf Rahman Al Hakim; Rachmad Sholeh; Mochamad Irfan; Sugeng Eko Yuli Waluyo; Elok Cahyaning Pratiwi (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This community service aims to empower women members of the Mojokerto Women's School (SEKOPER) through human resource management (HRM) and digital marketing training. SEKOPER, as a women's community, has great potential but still faces challenges in managing its business effectively and efficiently. This community service is based on the identification of the needs of SEKOPER members related to the lack of knowledge in the fields of HRM and digital marketing. The method used in this community service is through direct training for SEKOPER members. The training materials include HRM and digital marketing modules that are specifically designed to meet the needs of members. In addition, initial needs mapping was carried out to ensure the relevance of the material presented. The implementation of the training involved competent speakers in their fields and used interactive learning methods. The results of the community service showed an increase in SEKOPER members' understanding of the importance of good human resource management and the use of digital technology in marketing. There were positive changes in behavior, such as members' efforts in planning HR needs and implementing digital marketing strategies. In addition, the formation of a collaborative network between members is also one of the positive impacts of this program. Overall, this community service shows that human resource management and digital marketing training can be an effective effort in empowering SEKOPER women members. With increased capacity, it is hoped that SEKOPER members can improve their quality of life and family economic welfare.